Enantioselective silver-catalyzed cascade synthesis of fused lactone and lactam oxazolines - De La Campa, R; Manzano, R; Calleja, P; Ellis, SR; Dixon, DJ (American Chemical Society, 2018)
A new and highly stereoselective cascade reaction between isocyanoacetate esters and α-hydroxy and α-amino ketones has been developed. A cinchona alkaloid derived aminophosphine/silver(I) catalyst complex promoted the reaction and enabled the ready synthesis of fused bicyclic γ-lactone and γ-lactam oxazolines with high enantiocontrol (up to 99% ee).